Role of green chemistry in sustainable corrosion inhibition: a review on recent developments. (December 2022) - Al Jahdaly, Badreah A.; Maghraby, Yasmin R.; Ibrahim, Ahmed H.; Shouier, Kamel R.; Alturki, Asma M.; El-Shabasy, Rehan M.
Abstract: Application of corrosion inhibitors is one of the most feasible ways for metal protection against corrosion reactions. The corrosion inhibitors have the ability to get adsorbed on metal surfaces causing inhibition of corrosion mainly through the blockage of many active sites. The tremendous drawbacks associated with the application of organic corrosion inhibitors, especially the significant toxicity to the environment, have significantly enhanced further examination of biodegradable and safe alternatives, such as the usage of green and sustainable inhibitors. Secondary metabolites and phytochemicals that can be extracted from diverse plant species can be used for this specific regard. The naturally extracted phytochemicals have several advantages, namely being environmentally friendly, ecologically acceptable, low cost, abundantly available, easily renewable, and so on. The current review complies the latest literature and scientific reports entailing topics about the protection effectiveness, techniques of adsorption and inhibition mechanism of specifically plant extracts and wastes to be used as corrosion inhibitors. Several plant species are discussed for usage as corrosion inhibitors, attributed to their several naturally constituted phytochemicals. This review also discusses some synergistic effects of diverse plant extracts in alleviating corrosion reactions.